Modelling, Construction and Manufacture of a Lightweight Robot Arm - Hagenah, Hinnerk; Böhm, Wolfgang; Breitsprecher, Thilo; Merklein, Marion; Wartzack, Sandro (Proceedings of the 8th CIRP International Conference on Intelligent Computation in Manufacturing Engineering, 2012)
This contribution will show how modern materials as cellular titanium and nanocrystalline aluminium can be used to build advanced lightweight robot arms. Cellular titanium allowing a specific density distribution and the manufacture of fine structures with desirable properties is produced by selective electron beam melting while the nanocrystalline aluminium results from accumulative roll bonding. The specific properties of both materials will be highlighted. The paper will cover the definition of the product specification, the setting of a basic design and the optimisation of this by means of topology optimisation. This optimisation requires an intelligent modelling to be able to investigate different initial settings and boundary conditions. The optimised part will then be finished with regards to manufacturability. The paper will close with a brief report about the actual manufacture of one of the investigated variants.
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.modell